DIGITAL ECONOMY: ESSENCE AND FEATURES OF FORMATION - Савчук, Світлана (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
The article considers the phenomenon of digital economy as one of the conditions for doing business in the modern world. The digital economy is considered from the standpoint of historical retrospect. The formation of the digital economy under the influence of technological development of innovations is analyzed. It is established that digitalization gets its place in the history of technological development, but unlike automation and earlier technological transformations, digitalization goes far beyond production and covers other phases of the reproduction cycle. The concept of digital economy is analyzed and its essence is defined. The dynamics of indicators of digital economy development in Ukraine for the last three years is studied. It is established that these indicators have positive dynamics, in particular, the volume of sales received from trade through websites or applications increased by 28.4% to 4.5% of total sales. Based on the trends in the emergence and development of digital technologies, an analysis of the advantages and disadvantages of the digital economy. The advantages include: increasing the welfare of the population, reducing transaction costs, stimulating innovation, opening new markets, global automation and standardization of all economic processes: industrial, educational, medical, social, reducing bureaucracy and corruption, etc. The disadvantages include: destabilization of the monetary system; increasing dependence on leading companies in the field of information and communication technologies, etc. It is concluded that digital technologies are constantly being improved and integrated into global networks, integrated into various spheres of society. and change the global economy. Digitization should be seen as a tool, not an end in itself. With a systematic approach, digital technologies will stimulate the development of an open information society as one of the significant factors in increasing productivity, economic growth, job creation, and improving the quality of life of Ukrainian citizens.